2014
DOI: 10.3389/fnagi.2014.00088
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain barrier disruption: mechanistic links between Western diet consumption and dementia

Abstract: Both obesity and Alzheimer’s disease (AD) are major health burdens in Western societies. While commonly viewed as having separate etiologies, this review highlights data suggesting that intake of “Western diets”, diets high in saturated fatty acids (SFA) and simple carbohydrates, may pose a common environmental risk factor contributing to the development of both of these adverse pathologies. We discuss the effects of Western Diet intake on learning and memory processes that are dependent on the hippocampus, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 56 publications
(73 reference statements)
3
103
0
1
Order By: Relevance
“…In fact, several reports have also proposed that BBB impairment may serve as a critical link between HF diet consumption and Alzheimer’s disease pathology [120,121]. A few papers have used rodent models to directly link HF diet consumption to BBB integrity and cognition [90,91,92].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In fact, several reports have also proposed that BBB impairment may serve as a critical link between HF diet consumption and Alzheimer’s disease pathology [120,121]. A few papers have used rodent models to directly link HF diet consumption to BBB integrity and cognition [90,91,92].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In apolipoprotein E ε3 and ε4 knock-in mice 44 -45 weeks of cholesterol enriched diet increases levels of brain cholesterol esters especially in APOE ε4 knock-in mice [4]. Moreover it has been reported that dietary and metabolic factors are implicated in the damage of the blood brain barrier (BBB), which is a system of microvascular endothelial cells that protects the brain from toxic substances, limiting the entry of unwanted blood components [5]. Thus there could be a mechanistic link among Western diet consumption (high in saturated fatty acids), BBB impairment and learning and memory deficits, and possible the onset of a dementia [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…The BBB secures the brain's immune-privileged status by restricting the entry of peripheral inflammatory mediators such as cytokines and antibodies. The BBB is composed of specialized endothelial cells of the cerebral microvasculature, surrounding pericytes, astrocytic endfeet, perivascular macrophages, microglia, the basement membrane, and cell-cell junctions (Keller, 2013;Najjar et al, 2013;Hsu and Kanoski, 2014;Williams et al, 2014). As mentioned above, inflammation-mediated damage leads to BBB hyperpermeability, and S100 calcium-binding protein A4 (S100A4) may play a role in the induction of BBB disruption caused by the inflammation associated with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%